Urbanization, Physical Activity, and Metabolic Health in Sub-Saharan Africa - Félix Assah; Ulf Ekelund; Søren Brage; Jean Claude Mbanya; Nicholas J. Wareham (2011)
We examined the independent associations between objectively measured free-living physical activity energy expenditure (PAEE) and the metabolic syndrome in adults in rural and urban Cameroon.PAEE was measured in 552 rural and urban dwellers using combined heart rate and movement sensing over 7 continuous days. The metabolic syndrome was defined using the National Cholesterol Education Program-Adult Treatment Panel III criteria.Urban dwellers had a significantly lower PAEE than rural dwellers (44.2 ± 21.0 vs. 59.6 ± 23.7 kJ/kg/day, P < 0.001) and a higher prevalence of the metabolic syndrome (17.7 vs. 3.5%, P < 0.001). In multivariate regression models adjusted for possible confounders, each kJ/kg/day of PAEE was associated with a 2.1% lower risk of prevalent metabolic syndrome (odds ratio 0.98, P = 0.03). This implies a 6.5 kJ/kg/day difference in PAEE, equivalent to 30 min/day of brisk walking, corresponds to a 13.7% lower risk of prevalent metabolic syndrome. The population attributable fraction of prevalent metabolic syndrome due to being in the lowest quartile of PAEE was 26.3% (25.3% in women and 35.7% in men).Urban compared with rural residence is associated with lower PAEE and higher prevalence of metabolic syndrome. PAEE is strongly independently associated with prevalent metabolic syndrome in adult Cameroonians. Modest population-wide changes in PAEE may have significant benefits in terms of reducing the emerging burden of metabolic diseases in sub-Saharan Africa.